PENGARUH PENERAPAN MEDIA SCRAPBOOK TERHADAP TINGKAT KECEMASAN ANAK PRA SEKOLAH HOSPITALISASI DI RSU SEMBIRING DELI TUA KECAMATAN DELI TUA KABUPATEN DELI SERDANG TAHUN 2024 - Barus, Dewi Tiansa; Purba, Rentawati; Silalahi, Rini Debora (Jurnal Inovasi Kesehatan Masyarakat, 2024)
When a kid is admitted to the hospital, either as an emergency or as part of a plan, they stay there until their condition gets better and they are able to return home. Anxiety is one of the effects of hospitalization on a child. Children's most frequent concerns include excessive weeping, fear of strangers and the police, and anxiety. Scrapbook play therapy is one intervention that may be used to help kids who are anxious about being sent to the hospital. This study sought to ascertain how play therapy using Scrapbook media affected the anxiety levels of preschoolers admitted to hospitals. With a special group pretest and posttest design, this study employed a pretest strategy. Purposive sampling of pediatric patients receiving care at Sembiring General Hospital was the sample strategy employed in this study, which included 18 responders in total. The youngster received a 30-minute intervention once a day during their spare time. Results: A p-value of less than 0.000 (less than 0.05) was obtained using the Shapiro-Wilk test. The study's result is that preschoolers hospitalized in RSU Sembiring Deli Tua, Deli Tua District, Deli Serdang Regency in 2024 would have lower anxiety levels due to the use of Scrapbook media.